Integrated copper-halide activated scintillator fiber array for remote high-resolution X-ray imaging - Hao Zhang; Xiongjian Huang; Tianze Wan; Ruishan Wei; Bozhao Yin; Yakun Le; Shengda Ye; Weiwei Chen; Mingjia Li; Xiudi Xiao; Xiaofeng Liu; Zhiguo Xia; et al. (Nature Communications)
Abstract Long-distance transmission scintillator arrays enable high-resolution X-ray imaging and signal transmission in challenging environments such as aerospace machinery, nuclear reactor cores, and complex biological regions. However, advanced scintillator arrays are still limited to thin films and blocks, which are unable to simultaneously support both imaging and long-distance transmission functions. We address this limitation by designing scintillator active fiber arrays composed of glass embedded with Cs3Cu2X5 (X=Cl, Br, and I) nanocrystals. The scintillator glass forms through controlled crystallization of Cs3Cu2X5, and low-loss (~5 m) active fibers are engineered into an array of approximately 1,600 pixels with high resolution (48 lp mm−1; limit: 60.7 lp mm−1) via waveguide structuring. This detector penetrates complex structures and enables effective low-dose imaging. Our approach supports scalable, high-density fiber-optic X-ray arrays, providing a new platform for advanced imaging in both scientific and industrial applications.